Evidence for unusually thin oceanic crust and strong mantle beneath the Amazon Fan - Rodger, M; Watts, A; Greenroyd, C; Peirce, C; Hobbs, R (2006)
We used seismic and gravity data to determine the structure of the crust and mantle beneath the Amazon Fan. Seismic data suggest that the crust is of oceanic-type and is unusually thin (< ∼4 km) compared to elsewhere in the Atlantic. We attribute the thin crust to ultraslow seaffoor spreading following the breakup of South America and Africa during the Early Cretaceous. Gravity data suggest that the fan was emplaced on lithosphere that increased its elastic thickness, Te, and hence strength, following rifting. The increase, from 10 km to 40 km, is greater, however, than would be expected if Te were determined by a single controlling isotherm, based on a cooling plate model. Hence, we conclude that the Amazon Fan has been emplaced on, and is supported by, unusually thin oceanic crust and strong mantle. © 2006 Geological Society of America.